2019
DOI: 10.1371/journal.pone.0215506
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of the interaction between binge-eating and attention

Abstract: Objective To investigate whether binge-eating in patients with eating disorders (EDs) is associated with attentional deficits. Methods We studied ED patients with binge-eating (n = 51), no binge-eating (n = 59) and controls (n = 58). ED patients were assessed following the stabilization of weight and ED pathology. Attention assessment included evaluation of attention deficit hyperactivity disorder (ADHD) diagnosis, the Adult ADHD Self-Report (ASRS) and ADHD Rating Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Five studies assessed ADHD in clinical populations of women with ED. High ADHD prevalence was found, especially among women with ED involving binging/purging behavior (AN-BP, EDNOS-BP, BN): from 10.2% to 49.8% [120][121][122][123][124]. However, Halevy-Yosef and colleagues (2019) [122] observed no significant difference in terms of ADHD prevalence between ED patients with BE (16.6%) and those without BE (13.6%) (p = 0.392).…”
Section: Adultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Five studies assessed ADHD in clinical populations of women with ED. High ADHD prevalence was found, especially among women with ED involving binging/purging behavior (AN-BP, EDNOS-BP, BN): from 10.2% to 49.8% [120][121][122][123][124]. However, Halevy-Yosef and colleagues (2019) [122] observed no significant difference in terms of ADHD prevalence between ED patients with BE (16.6%) and those without BE (13.6%) (p = 0.392).…”
Section: Adultsmentioning
confidence: 93%
“…Six publications involved samples of individuals with ED. They found that ADHD symptomatology and diagnosis were associated with ED, especially binging/purging behaviors such as BN and AN binge/purge subtype, which were related to inattentive symptoms [122][123][124]. However, Halevy-Yosef and colleagues (2019) [122] found no differences in ASRS scores between ED with and without binging/purging behavior after Bonferroni correction.…”
Section: Adultsmentioning
confidence: 98%
See 3 more Smart Citations